Combined Optimized Effect of a Highly Self-Organized Nanosubstrate and an Electric Field on Osteoblast Bone Cells Activity. (21st March 2019) - Portan, Diana V.; Deligianni, Despina D.; Papanicolaou, George C.; Kostopoulos, Vassilis; Psarras, Georgios C.; Tyllianakis, Minos
Abstract : The effect of an electric field within specific intensity limits on the activity of human cells has been previously investigated. However, there are a considerable number of factors that influence the in vitro development of cell populations. In biocompatibility studies, the nature of the substrate and its topography are decisive in osteoblasts bone cells development. Further on, electrical field stimulation may activate biochemical paths that contribute to a faster, more effective self-adjustment and proliferation of specific cell types on various nanosubstrates. Within the present research, an electrical stimulation device has been manufactured and optimum values of parameters that led to enhanced osteoblasts activity, with respect to the alkaline phosphatase and total protein levels, have been found. Homogeneous electric field distribution induced by a highly organized titanium dioxide nanotubes substrate had an optimum effect on cell response. Specific substrate topography in combination with appropriate electrical stimulation enhanced osteoblasts bone cells capacity to self-adjust the levels of their specific biomarkers. The findings are of importance in the future design and development of new advanced orthopaedic materials for hard tissue replacement.